Cartera vencida en los predios urbanos del Gobierno Autónomo Descentralizado Municipal del Cantón Ventanas en el periodo 2022 - Romero Gaibor, Lady Lucelly (2023)
This study focuses on analyzing the overdue portfolio of urban properties in the Autonomous Decentralized Municipal Government of Ventanas Canton during the year 2022. The issue at hand revolves around the high accumulation of debts by taxpayers, negatively impacting municipal finances and the ability to carry out local projects and programs. The justification for this case study lies in the need to understand and address this financial challenge to ensure the effective functioning of municipal administration. The overall objective is to determine the current impact of the overdue portfolio of the Municipal GAD Government of Ventanas Canton during the year 2022 in order to identify the financial consequences and how they affect decision-making. To achieve this, a mixed-method methodology was employed, combining document review, interviews with key personnel, process observation, and financial data analysis. In conclusion, the importance of implementing proactive communication strategies, designing incentives for timely payments, and establishing personalized service units for taxpayers is highlighted. These recommendations aim not only to reduce the overdue portfolio but also to improve the relationship with citizens and optimize municipal resources.